NEED AND SCOPE FOR CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) AT THE TECHNICAL DIPLOMA LEVEL IN KERALA - George, Arun (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Technical diploma holders who come out of polytechnic colleges are expected to acquire theoretical and subject-based skills in addition to adequate English language skills. In reality, they lack many of these aspects. A method of teaching which supports both subject learning and language acquisition can help to overcome this inadequacy. Content and Language Integrated Learning (CLIL) is an instructional approach that combines subject matter instruction with language learning, leveraging the classroom environment to enhance both content and language skills. This learner-centred method necessitates the collaboration of content and language teachers to prepare and deliver integrated lessons effectively. In CLIL, content, communication, cognition, and culture are equally prioritized, allowing for flexibility and adaptation to meet specific contextual needs.